2013
DOI: 10.1055/s-0033-1348262
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defense in Overt and Subclinical Hypothyroidism

Abstract: Oxidative stress as a result of disequilibrium between free radical generation and antioxidant status has been implicated in several pathologies including thyroid diseases. Studies on antioxidant status in overt (OHT) and subclinical hypothyroidism (SHT) are controversial and limited. The aim of this study was to determine the effect of OHT and SHT on antioxidant status. Thirty-six patients with OHT, 36 patients with SHT, and 39 healthy euthyroid subjects as the control group were included in the study. Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 26 publications
5
39
0
2
Order By: Relevance
“…There are some data that show in patients with hypothyroidism, oxidative stress, is increased (Lampka et al 2006;Sarandol et al 2005), decreased (Venditti et al 1997) or remain unchanged (Coria et al 2009). In agreement with the results of the current study, Reddy, et al demonstrated that the serum level of MDA and GPx activity increase in hypothyroid and subclinical hypothyroid patients (Reddy et al 2013). Another study showed that lipid peroxidation increase and an antioxidant level decrease in blood of hypothyroid patients (Dumitriu et al 1988).…”
Section: Discussionsupporting
confidence: 92%
“…There are some data that show in patients with hypothyroidism, oxidative stress, is increased (Lampka et al 2006;Sarandol et al 2005), decreased (Venditti et al 1997) or remain unchanged (Coria et al 2009). In agreement with the results of the current study, Reddy, et al demonstrated that the serum level of MDA and GPx activity increase in hypothyroid and subclinical hypothyroid patients (Reddy et al 2013). Another study showed that lipid peroxidation increase and an antioxidant level decrease in blood of hypothyroid patients (Dumitriu et al 1988).…”
Section: Discussionsupporting
confidence: 92%
“…96 Although there is no evidence that antioxidants reduce vascular risk, it is of interest that severity of hypothyroidism appears to contribute to the antioxidant deficiency and oxidant stress. 97,98 SCH is related to non-alcoholic fatty liver disease (NAFLD) in a dose-dependent manner independently of metabolic risk factors. 99 Moreover, NAFLD and abnormal liver tests are associated with an increased risk of vascular events.…”
Section: Other Less Well Established Links Between Sch and Vascular Riskmentioning
confidence: 99%
“…OS has been implicated in the pathogenesis of over 100 human diseases, including endocrine disorders. 1,2 Diabetes is the most prevalent, leading endocrine disorder worldwide. Type 2 diabetes mellitus (DM) has been described as a global epidemic with the estimates of 171 million diabetics in 2000, expected an increase to 366-440 million by 2030.…”
Section: Introductionmentioning
confidence: 99%